2022
DOI: 10.1136/rapm-2021-103299
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning approach to predicting persistent opioid use following lower extremity joint arthroplasty

Abstract: BackgroundThe objective of this study is to develop predictive models for persistent opioid use following lower extremity joint arthroplasty and determine if ensemble learning and an oversampling technique may improve model performance.MethodsWe compared various predictive models to identify at-risk patients for persistent postoperative opioid use using various preoperative, intraoperative, and postoperative data, including surgical procedure, patient demographics/characteristics, past surgical history, opioid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…Previously published predictive models for extended postoperative opioid use-all based on retrospective data-show an average AUC of 0.76 for preoperative opioid use. [62][63][64][65][66][67][68][69][70][71][72][73] Our prospective models show that at 6 weeks post-TKA, preoperative opioid use is a less accurate predictor (AUC = 0.64) than prior retrospective models indicate, highlighting the importance of psychosocial and pain-related predictors at this time point. In contrast, at 6-month follow-up, preoperative opioid use is an even better prospective predictor than prior work would suggest (AUC = 0.90), and the addition of the above phenotypic characteristics improves it even further.…”
Section: Discussionmentioning
confidence: 58%
“…Previously published predictive models for extended postoperative opioid use-all based on retrospective data-show an average AUC of 0.76 for preoperative opioid use. [62][63][64][65][66][67][68][69][70][71][72][73] Our prospective models show that at 6 weeks post-TKA, preoperative opioid use is a less accurate predictor (AUC = 0.64) than prior retrospective models indicate, highlighting the importance of psychosocial and pain-related predictors at this time point. In contrast, at 6-month follow-up, preoperative opioid use is an even better prospective predictor than prior work would suggest (AUC = 0.90), and the addition of the above phenotypic characteristics improves it even further.…”
Section: Discussionmentioning
confidence: 58%
“…To this end, LLMs can be used to classify patients with persistent opioid use and can aid (1) in clinical decision support 9 ; and (2) as a critical step in developing accurate opioid prediction models. 10 Using NLP is a scalable solution for improving classification accuracy within large datasets, as the EHR reaches the status of “Big Data.”…”
Section: Discussionmentioning
confidence: 99%
“…The data included age (years), sex (male vs female), body mass index (kg/m 2 ), English-speaking, comorbidities, regional nerve block performance, general anesthesia, intraoperative ketamine, intraoperative total intravenous anesthesia, opioid consumption, and pain scores (11-point numeric rating scale [NRS] from 0 to 10). These features were included, as they were determined to be relevant to postoperative opioid use based on clinical judgement and previous research [ 14 , 15 ]. Opioid consumption, defined as total opioids consumed intraoperatively and in the PACU, was measured in intravenous morphine equivalents (MEQ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown surgical procedure as an independent risk factor for prolonged opioid use [4,19,20]. Other risk factors include preoperative opioids, tobacco use, gender, and mood disorders [21][22][23][24][25][26]. Although efforts are in place to standardize postoperative opioid prescriptions per surgical procedure [27], there continues to be a wide variety in the amount and duration of opioids prescribed and often in excess [1,[28][29][30][31]].…”
Section: Comparison To Prior Workmentioning
confidence: 99%